Infrared receptors in pyrophilous (“fire loving”) insects as model for new un-cooled infrared sensors - Klocke, David; Schmitz, Anke; Soltner, Helmut; Bousack, Herbert; Schmitz, Helmut (Beilstein Journal of Nanotechnology, 2011)
Beetles of the genus Melanophila and certain flat bugs of the genus Aradus actually approach forest fires. For the detection of fires and of hot surfaces the pyrophilous species of both genera have developed infrared (IR) receptors, which have developed from common hair mechanoreceptors. Thus, this type of insect IR receptor has been termed photomechanic and shows the following two special features: (i) The formation of a complex cuticular sphere consisting of an outer exocuticular shell as well as of a cavernous microfluidic core and (ii) the enclosure of the dendritic tip of the mechanosensitive neuron inside the core in a liquid-filled chamber. Most probably a photomechanic IR sensillum acts as a microfluidic converter of infrared radiation which leads to an increase in internal pressure inside the sphere, which is measured by a mechanosensitive neuron.A simple model for this biological IR sensor is a modified Golay sensor in which the gas has been replaced by a liquid. Here, the absorbed IR radiation results in a pressure increase of the liquid and the deflection of a thin membrane. For the evaluation of this model analytical formulas are presented, which permits the calculation of the pressure increase in the cavity, the deformation of the membrane and the time constant of an artificial leak to compensate ambient temperature changes. Some organic liquids with high thermal expansion coefficients may improve the deflection of the membrane compared to water.
Keywords: fire detection; forest fire; Golay cell; infrared sensor; pyrophilous insects

(untitled) - Schmitz, A.; Sehrbrock, A.; Schmitz, H. (Arthropod. Struct. Dev., 2007)

(untitled) - Gronenberg, W.; Schmitz, H. (Cell Tissue Res., 1999)

(untitled) - Schmitz, H.; Schmitz, A. (Landscope, 2002)

Proceedings of the Entomological Society of London 1915 - Poulton, E. B. (The habits of the Australian Buprestid "Fire-beetle", Merimna atrata, 1915)

(untitled) - Apel, K.-H. (Entomol. Nachr. Ber., 1989)

(untitled) - Schmitz, H.; Bleckmann, H. (Int. J. Insect Morphol. Embryol., 1997)

(untitled) - Schmitz, H.; Schmitz, A.; Bleckmann, H. (Arthropod. Struct. Dev., 2001)

(untitled) - Schmitz, H.; Trenner, S. J. (Comp. Physiol., A, 2003)

(untitled) - Schütz, S.; Weissbecker, B.; Hummel, H. E.; Apel, K.-H.; Schmitz, H.; Bleckmann, H. (Nature, 1999)

(untitled) - Schmitz, H.; Schmitz, A.; Trenner, S.; Bleckmann, H. (Naturwissenschaften, 2002)

(untitled) - Kreiss, E.-J.; Schmitz, A.; Schmitz, H. (Arthropod. Struct. Dev., 2005)

(untitled) - Schmitz, A.; Schätzel, H.; Schmitz, H. (Arthropod. Struct. Dev., 2010)

(untitled) - Champion, G. C. (Ent. Mo. Mag., 1909)

(untitled) - Linsley, E. G. J. (Econ. Entomol., 1943)

(untitled) - Evans, W. G. (Pan-Pac. Entomol., 1962)

(untitled) - Vondran, T.; Apel, K.-H.; Schmitz, H. (Tissue Cell, 1995)

(untitled) - Schmitz, H.; Bleckmann, H. J. (Comp. Physiol., A, 1998)

(untitled) - Schmitz, H.; Mürtz, M.; Bleckmann, H. (Nature, 1997)

(untitled) - Evans, W. G. (Ann. Entomol. Soc. Am., 2005)

(untitled) - Keil, T. A. (Microsc. Res. Tech., 1997)

(untitled) - Golay, M. J. E. (Rev. Sci. Instrum., 1947)

(untitled) - Chevrier, J. B.; Baert, K.; Slater, T. (J. Micromech. Microeng., 1995)

(untitled) - Kenny, T. W.; Reynolds, J. K.; Podosek, J. A.; Vote, E. C.; Miller, L. M.; Rockstad, H. K.; Kaiser, W. J. (Rev. Sci. Instrum., 1996)

Handbook of Chemistry and Physics - Lide, D. R. (Section 6: Fluid Properties, 2006)

Höhere technische Mechanik: nach Vorlesungen - Szabo, I. (Springer, 2001)

Proceedings - Soltner, H.; Bousack, H.; Schmitz, H. (Zur transienten Temperaturentwicklung in einem fluidischen Infrarot-Detektor auf der Basis der infrarotempfindlichen Sensillen des Schwarzen Kiefernprachtkäfers Melanophila acuminata, MikroSystemTechnik KONGRESS 2009, Berlin, 12.10.2009-14.10.2009, 2009)

(untitled) - Wieliczka, D. M.; Wenig, S.; Querry, M. R. (Appl. Opt., 1989)

National Institute of Standards and Technology (NIST), Chemistry WebBook

Quick reference manual for silicon integrated circuit technology - Beadle, W. E.; Tsai, J. C. C.; Plummer, R. D. (Wiley, 1985)

Biophysik – ein Lehrbuch - Thurm, U. (Mechano-elektrische Transduktion, 1982)

Capacitive Position Sensor for Nanopositioning – MicroSense Mini, MicroSense LLC, Massachusetts, USA.

Fluid Mechanics - Spurk, J. H.; Aksel, N. (Springer, 2008)

Actuator 2008: Proceedings - Bousack, H.; Schmitz, H.; Offenhäuser, A. (Design of a fluidic infrared detector based on the infrared sensilla in the beetle Melanophila acuminata, 11th International Conference on New Actuators, Bremen, 27.6.2008-30.6.2008, 2006)